Peripartum cardiomyopathy: Characteristics and outcomes among women seen at a referral hospital in Lusaka, Zambia. (October 2022) - Strasserking, Fiona E.; Musho, Jane; Heimburger, Douglas C.; Mutale, Wilbroad; Damp, Julie A.; Mumba, Ngosa; Goma, Fastone
Abstract: Background: Peripartum cardiomyopathy (PPCM) disproportionately affects women of African descent, however knowledge about this disease in African countries is limited. Objectives: To describe the phenotype of women with PPCM seen at a referral hospital in Zambia and examine outcomes at 6 months. Methods: A prospective observational study describing characteristics and 6-month outcomes was performed at the University Teaching Hospital Echocardiography Lab in Lusaka, Zambia. Results: We enrolled 45 participants with PPCM and 38 were seen at 6-month follow up; 3 (7 %) died and 4 (9 %) were lost to follow up. Mean age was 32.9 years (SD:7.0); mean BMI was 25.3 kg/m 2 (SD:4.1), mean parity was 3.4 (SD:2.2) children and twin pregnancies occurred in 4 (9 %). Median time from symptom onset to diagnosis was 60 days (IQR: 1–280). 20 (44 %) reported gestational hypertension and 10 (22 %) reported preeclampsia. Baseline median left ventricular ejection fraction (LVEF) was 36 % (IQR: 11–45), median left ventricular end-diastolic volume (LVEDV) was 150 mL (IQR: 58–229) and 79 % described New York Heart Association (NYHA) functional class IV symptoms. Median LVEF after 6 months was 49 % (IQR: 23–68; p < 0.001) and median LVEDV was 121 mL (IQR: 66–200; p < 0.001). At 6-month follow up 45 % had LVEF ≥ 50 %, 42 % had LVEDV ≤ 106 mL and 1 (3 %) had NYHA functional class IV symptoms. Conclusions: Hypertension was prevalent in this cohort. Overall mortality rate was low and clinically significant improvements in cardiac parameters were seen in over 40%. Further research is needed to identify and mitigate gaps in diagnosis and management.